Circular economy in post consumption network: the role of re-commerce groups in social media platforms - Xie, Ying; Arman, Saleh Md; Su, Chang (Elsevier, 2025)
The success of the circular economy transition depends on the involvement of all stakeholders. However, research on consumer participation in the circular economy is limited. This study identifies the micro-level dynamics of the circular economy within the post-consumption network, mainly focusing on re-commerce operations. Through exploring re-commerce networks in 20 countries and a statistical analysis of factors influencing sales performances on Facebook, this research aims to identify the primary elements influencing re-commerce activities on Facebook and their role in promoting circular economy. This study uses grounded theory and a mixed-methods approach, combining literature reviews and interviews, to explore the impact of re-commerce on the circular economy. Based on the research findings, this research develops four propositions to promote future research on post-consumption networks in the circular economy context.
Keywords: 46 Information and Computing Sciences; 38 Economics; 12 Responsible Consumption and Production; Information Systems; 38 Economics; 46 Information and computing sciences; Circular economy; consumer; econometric model; Facebook; post-consumption; re-commerce